Lipoma in the pelvic limb of a cat: Case report - Duarte, Oksana; Corrêa Kuci, Cristina; Giusti Schran, Roberta (Pubvet, 2024)
Lipomas are benign masses primarily composed of adipocytes and are common in dogs, their occurrence in cats being less reported. Despite being generally considered harmless, lipomas can cause symptoms related to mechanical restriction or discomfort in patients. This study presents a case report of a lipoma in a cat, where the diagnosis was confirmed by cytology and histopathology. Surgery was indicated as treatment, with the application of Evans blue for lymphatic identification of the mass. Although lipomas are usually benign in nature, their occurrence and the involvement of specific cellular subtypes in their development are discussed in this report, emphasizing the need for a better understanding of cellular composition and biological activities in lipoma tissues in felines, highlighting the importance of the complete surgical excision described by us, and the need for further research on the cellular composition of lipomas in cats.
Keywords: Cells CD34+; cat; histopathology; lipoma